MAKNA PENGGUNAAN MAKE-UP SEBAGAI IDENTITAS CANTIK (STUDI PADA MAHASISWI FISIP UNIVERSITAS UDAYANA) - Wahyuwidowati, Nifita Sistin; Nugroho, Wahyu Budi; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 1 No 2 (2019), 2020)
ABSTRACT Students want to look beautiful in everything, one of the efforts made to look beautiful using makeup. This research discusses to understand the meaning of using make up as a beautiful identity and driving factors as well as the use of make up for farmers. This research was conducted at Udayana University, using descriptive qualitative research methods. Data collection techniques used were interviews, observation, documentation, and literature. The sampling technique uses purposive sampling. Research subjects are female students and make-up beauty advisors. Data validity uses source triangulation and data analysis uses Miles and Huberman interactive. The results showed that the use of make up gave rise to internal factors namely physical deficiencies and liking for make up, and external factors were affecting friends, parents, beauty vloggers, and improving work and organization. The meaning of using make up is the importance to look perfect, get personal attention and satisfaction. Keywords: makeup, personal identity, impact